RESPON PERTUMBUHAN DAN HASIL CABAI RAWIT PADA PENGGUNAAAN PUPUK FOSFAT CEPAT LARUT DAN PUPUK KANDANG - Achmad Fatchul Aziez; ongko cahyono; Dwi Susilo Utami; Agus Budiyono; Sapto Priyadi; Daryanti; Nurul Ida Cahyani (JURNAL ILMIAH AGRINECA, 2021)
Cayenne pepper (Capsicum frutescens L.) was a plant that has high economic value. The application of phosphate fertilizers in inorganic forms is not friendly to the environment and is slowly available to plants. This research was carried out from October 2019 to January 2020 in Pancot Village, Kalisoro Village, Tawangmangu District, Karanganyar Regency with an altitude of 1200 meters above sea level and Andisol soil type. This study used a completely randomized design with two treatment factors (factorial), namely the first factor is the dose of fast soluble phosphate fertilizer namely 0 kg/ha (no SP36 fertilizer), 150 kg/ha (one application), 150 kg/ha (3 times application), 100 kg/ha (3 times application), and 50 kg/ha (3 times application). The second factor is the dose of chicken manure consisting of 2 levels, namely 0 tons/ha (no chicken manure), and 40 tons/ha. Parameters observed were plant height, flowering age, fresh weight of the plant, number of branches, and number of fruit per plant. The results showed that fast soluble phosphate fertilizer had a very significant effect on plant fresh weight and fruit number. Manure treatment has a significant effect on the parameters of plant height, fresh weight of the plant, total fruit per plant. The interaction of fast soluble phosphate fertilizer and manure had a significant effect on flowering age, fresh weight, and the number of fruits per plant. The best results were in the interaction of fast soluble phosphate fertilizer with a dose of 50 kg/ha and 40 tons/ha of manure.